Modern trends in physics research 4th International Conference on Modern Trends in Physics Research, MTPR-10, Cairo University, Egypt, 12-16 December 2010 - El Nadi, Lotfia (AIP conference proceedings, 2013)
The objectives of the conference are to develop greater understanding of physics research and its applications to promote new industries; to innovate knowledge about recent breakthroughs in physics, both the fundamental and technological aspects; to implement of international cooperation in new trends in physics research and to improve the performance of the physics research facilities in Egypt. This proceedings highlights the latest results in the fields of astrophysics, atomic, molecular, condensed matter, lasers, nuclear and particle physics. The peer refereed papers collected in this volume were written by international experts in these fields.